The Impact Of Online Game Addiction On Elementary School Students' Learning Motivation: A Qualitative Study Of Grade 5 Students At SDN Karangmakmur III - Chandra Sagul Haratua; Abdul Aziz; Rudiawan Prawira; Jejen Tabriji; Henny Ambarwati; Ahmad Nurhadi (Universitas Palan, 2024)
This study aims to examine the impact of online game addiction on the learning motivation of fifth-grade students at SDN Karangmakmur III. A qualitative approach was used to gain in-depth understanding through in-depth interviews, observations, and document analysis. The results show that the majority of students addicted to online games experience a significant decline in learning motivation. This is reflected in their low academic performance, lack of concentration in class, and minimal participation in school activities. Parental support and teacher involvement are crucial in maintaining students' learning motivation. Recommended intervention strategies include healthy technology education, limiting game playing time, and promoting alternative activities. Collaboration between teachers, parents, and school authorities is essential to mitigate the negative impact of online game addiction and enhance students' learning motivation.